If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-9j + -18) = -20j + -2(18j + 4) Reorder the terms: 6(-18 + -9j) = -20j + -2(18j + 4) (-18 * 6 + -9j * 6) = -20j + -2(18j + 4) (-108 + -54j) = -20j + -2(18j + 4) Reorder the terms: -108 + -54j = -20j + -2(4 + 18j) -108 + -54j = -20j + (4 * -2 + 18j * -2) -108 + -54j = -20j + (-8 + -36j) Reorder the terms: -108 + -54j = -8 + -20j + -36j Combine like terms: -20j + -36j = -56j -108 + -54j = -8 + -56j Solving -108 + -54j = -8 + -56j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '56j' to each side of the equation. -108 + -54j + 56j = -8 + -56j + 56j Combine like terms: -54j + 56j = 2j -108 + 2j = -8 + -56j + 56j Combine like terms: -56j + 56j = 0 -108 + 2j = -8 + 0 -108 + 2j = -8 Add '108' to each side of the equation. -108 + 108 + 2j = -8 + 108 Combine like terms: -108 + 108 = 0 0 + 2j = -8 + 108 2j = -8 + 108 Combine like terms: -8 + 108 = 100 2j = 100 Divide each side by '2'. j = 50 Simplifying j = 50
| 7(-1+4x)=77 | | 11j=-6j-15 | | 2x+8+4x=20 | | 6(-9j-18)=-20j-2(18+4) | | -5(y+1)=5 | | 6(-9j-18)=20j-2(18+4) | | 5(8-4x)=-100 | | -3(-16z+20)-19z=20z-6 | | -8+6x=3x-5 | | 3(1)-2(-2+7)=-7 | | -15w-9.65=-8.6w+3.4w+9.95 | | y=0+60x | | y=150+35x | | -14.7f=0.24-12.3f | | 288+9y=18 | | -2(5x-10)=70 | | -12x+2y=-4x+10 | | X^2=13x+220 | | -15.45-11.7q=-11.1q-4.05 | | -2(n-2)+4=64 | | 36x+3=5 | | (9x^2)-(x)+9=0 | | 10*3y-2=4y-y+8 | | 16.2-3.8g=-11.9g | | 7(5-x)=42 | | 6b^2+45b=0 | | 3+-3=3t+6 | | 0.7x-1=(-0.5x-0.7) | | 15.85+1.8y=-0.2y-18.67-1.08 | | (2x^2)-(9x)+10=0 | | -8s=-10s+14 | | 6x-9=39-2x |